Chromium: Rise and Shine in Peritoneal Dialysis Patients?. Issue 4 (July 2019) - Filler, Guido; McIntyre, Christopher
Some trace elements are altered with chronic kidney disease. Selenium, zinc, and manganese tend to be wasted, and there is growing evidence that selenium deficiency is associated with mortality on dialysis. Other trace elements accumulate, such as chromium, cobalt, lead, molybdenum, and vanadium. The highest chromium levels are found in dialysis patients. The dialysis modality may further affect these levels, especially in hemodialysis patients, where even small contaminations in the dialysis feed water may lead to a concentration gradient that increases the concentration of certain trace elements. Chromium levels in peritoneal dialysis (PD) patients have been understudied. A single cross-sectional study found substantially higher chromium levels in PD patients. In that study, the chromium concentration in the spent dialysate decreased substantially, suggesting that PD fluid could be a source of chromium. Chromium-lactate complexes may have been formed, which are easily absorbed. In our center, we observed a decrease in chromium level when using physiological PD fluids. This review discusses the potential mechanisms and raises the question of whether this accumulation of chromium is unlikely to be associated with a beneficial outcome.